Exergetic optimization of a flat plate solar collector design - Sia, Toh Ching; Velautham, Sanjayan; Nordin, Amer (Regional Energy Resources Information Center, 2007)
It has been established that energy efficiency of a flat plate solar collector increases without extremum points with the flow rate and likewise the fluid outlet temperature increases with the collecting area. Thus, it provides no maximum points for the purpose of optimization of solar collector design. In contrast, exergy analysis presents various local points forhex = f(m,Ac), and with a global maximum point. Based on these findings, this paper further develops the exergy analysis of a flat plate solar collector by outlining the correlation between the exergy efficiency of a flat plate solar collector, hex ,with the outlet and inlet fluid temperature variation, âˆ†T, with respect to the influence of fluid flow rate, m , and collector area, Ac. In addition, the inter-relation between the fluid flow rate and the collector area is also examined as a ratio, R, where R = m/Ac , thus, giving hex = f(R) and DT = f(R) . From these evaluations, it seems that there is a precise value of R which will give the optimum operating mode for the solar collector, either with maximum exergy efficiency or maximum temperature variation, or both, for a fixed design specification. The value of R and the corresponding values of exergy efficiency and temperature variation are evaluated in this paper for Malaysia meteorological conditions.